Knowledge, attitude, and practices of nursing mothers toward breastfeeding in a tertiary care center in Navi Mumbai - Sharif, Mumtaz; Saxena, Amit; Nair, Shweta; Sharma, Ashok; Jain, Prashant (Indian Journal of Child Health, 2022)
Objective: Breastfeeding (BF) has been accepted as the most vital intervention for reducing infant mortality and ensuring optimal growth and development of a child. A major barrier to successful BF is inconsistency in information and improper cultural practices. To assess the knowledge, attitude, and practices toward BF among nursing mothers following up in a tertiary care center in Navi Mumbai, Maharashtra. Methods: A community-based cross-sectional study was conducted among 512 mothers in Navi Mumbai in the state of Maharashtra, India, between January 2016 and June 2016 using a pre-set questionnaire. The mothers with children under the age of 2 years were interviewed following which descriptive statistics were obtained. Results: Our study highlights the growing awareness of the advantages of BF. Of the 512 mothers enrolled in our study, 78.9% believed in exclusive BF (EBF) till 6 months while 51% actually practiced EBF. Nearly 78% mothers felt shy to feed in public places. BF was initiated <1 h of delivery in 35.9% mothers while insufficient milk was the predominant reason (41.4%) in mothers to stop BF before 2 years. Conclusion: The majority of our participants had adequate knowledge and a positive attitude toward EBF, with right posture practiced while feeding.